(untitled) (Studia theodisca, 2012)
In the George-Kreis the category of “Gestalt” is often employed as a hermeneutic criterion for the interpretation of great authors of the past. Starting from the presence of the term “Gestalt” at various places in George’s translations from the Divina Commedia, which accompanied his poetic work for a long time, this article aims at reconstructing the way in which the paradigm of “Gestalt” fluctuates between the fields of historiographic inquiry and literary invention.